2015
DOI: 10.18831/djcivil.org/2015011004
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Construction in Metro based on Planning and Management

Abstract: In the present days, majority of the construction projects can be considered as complex and compose of vague efforts. The construction project of each kind has its own properties and issues. At the same time different approaches in specific management and settlement are required. About the cities and their rapid development, construction of underground at urban regions such as construction in metro have been often used for extending daily human life into spaces of underground. Hence, the complex element recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It also demonstrates the critical arrival rates to separate the three mentioned modes to decrease the congestion at intersection points. [10] has investigated the complications in the construction of subways. [11] has concluded that the speed of motorcycles and scooters are 10% faster than the remaining vehicles and also has higher tendency to break speed limits and violate lanes leading to more number of two-wheeler accidents.…”
Section: Relevant Workmentioning
confidence: 99%
“…It also demonstrates the critical arrival rates to separate the three mentioned modes to decrease the congestion at intersection points. [10] has investigated the complications in the construction of subways. [11] has concluded that the speed of motorcycles and scooters are 10% faster than the remaining vehicles and also has higher tendency to break speed limits and violate lanes leading to more number of two-wheeler accidents.…”
Section: Relevant Workmentioning
confidence: 99%